GREEN CONSUMPTION–BASED POLICY STRATEGIES FOR GREEN ECONOMY DEVELOPMENT IN YOGYAKARTA CITY - Haryanto Haryanto; Dessy Rachmawatie; Ahmad Ma'ruf (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
This study aims to examine the effects of green purchase intention and environmental knowledge on green purchase behavior in Yogyakarta City and to formulate evidence-based green economy policy strategies. The research adopts an explanatory quantitative approach using an online survey of 401 respondents with experience purchasing environmentally friendly products from micro, small, and medium enterprises (MSMEs). Multiple linear regression analysis was employed to test the causal relationships among variables, and the empirical findings were subsequently integrated into a SOAR (Strengths, Opportunities, Aspirations, Results) analysis to develop operational policy strategies. The results indicate that both green purchase intention and environmental knowledge have positive and significant effects on green purchase behavior, with environmental knowledge emerging as the most dominant determinant. These findings suggest that green purchase behavior provides a robust empirical foundation for demand-side green economy policies. The SOAR analysis further highlights strategic directions emphasizing environmental literacy strengthening, pilot projects for green consumption, and the integration of MSMEs and tourism sectors into an urban green economy ecosystem. This study contributes to the literature by linking consumer behavior evidence with practical green economy policy formulation at the local level.